Transition from Acute to Chronic Tinnitus: Predictors for the Development of Chronic Distressing Tinnitus - Wallhäusser-Franke, Elisabeth; D’Amelio, Roberto; Glauner, Anna; Delb, Wolfgang; Servais, Jérôme J.; Hörmann, Karl; Repik, Ines (Frontiers in Neurology, 2017)
Background Acute tinnitus and its transition to chronic tinnitus are poorly investigated, and factors associated with amelioration versus exacerbation are largely unknown. Aims of this study were to identify early predictors for the future development of tinnitus severity. Method Patients with tinnitus of no longer than 4 weeks presenting at an otolaryngologist filled out questionnaires at inclusion (T1), as well as 3 (T3), and 6 months (T4) after tinnitus onset. 6 weeks after onset, an interview was conducted over the phone (T2). An audiogram was taken at T1, perceived tinnitus loudness, and tinnitus-related distress were assessed separately and repeatedly together with oversensitivity to external sounds and the levels of depression and anxiety. Furthermore, coping strategies with illness were recorded. Results Complete remission until T4 was observed in 11% of the 47 participants, while voiced complaints at onset were stable in the majority. In the subgroup with a relevant level of depression at T1, tinnitus-related distress worsened in 30% until T4. For unilateral tinnitus, perceived loudness in the chronic condition correlated strongly with hearing loss at 2 kHz on the tinnitus ear, while a similar correlation was not found for tinnitus located to both ears or within the head. Conclusion Results suggest early manifestation of tinnitus complaints, and stress the importance of screening all patients presenting with acute tinnitus for levels of depression and tinnitus-related distress. Furthermore, hearing levels should be monitored, and use of hearing aids should be considered to reduce tinnitus loudness after having ascertained that sound sensitivity is within normal range.